Efficient quantum dot light-emitting diodes with a Zn0.85Mg0.15O interfacial modification layer. Issue 26 (26th May 2017) - Sun, Yizhe; Jiang, Yibin; Peng, Huiren; Wei, Jiangliu; Zhang, Shengdong; Chen, Shuming
Abstract : Efficient inverted QLEDs have been developed by using solution processed ZnMgO nanoparticles as an interfacial modification layer. Abstract : Efficient inverted quantum-dot (QD) light-emitting diodes (LEDs) are demonstrated by using 15% Mg doped ZnO (Zn0.85 Mg0.15 O) as an interfacial modification layer. By doping Mg into ZnO, the conduction band level, the density of oxygen vacancies and the conductivity of the ZnO can be tuned. To suppress excess electron injection, a 13 nm Zn0.85 Mg0.15 O interlayer with a relatively higher conduction band edge and lower conductivity is inserted between the ZnO electron transport layer and QD light-emitting layer, which improves the balance of charge injection and blocks the non-radiative pathway. Moreover, according to the electrical and optical studies of devices and materials, quenching sites at the ZnO surface are effectively reduced by Mg-doping. Therefore exciton quenching induced by ZnO nanoparticles is largely suppressed by capping ZnO with Zn0.85 Mg0.15 O. Consequently, the red QLEDs with a Zn0.85 Mg0.15 O interfacial modification layer exhibit superior performance with a maximum current efficiency of 18.69 cd A −1 and a peak external quantum efficiency of 13.57%, which are about 1.72- and 1.74-fold higher than 10.88 cd A −1 and 7.81% of the devices without Zn0.85 Mg0.15 O. Similar improvements are also achieved in green QLEDs. Our results indicate that Zn0.85 Mg0.15 O can serve as an effective interfacial modification layer for suppressing exciton quenching and improving the charge balance of the devices.